Neurointerventional Surgery An Evidence Based Approach - Abecassis, I. Joshua (Thieme Medical Publishers, Inc., 2021)
Unique neurointerventional surgery resource analyzes landmark literature to inform optimal patient management The field of neurointerventional surgery is rapidly expanding with an ever-accelerating pace of technological innovations. While industry plays a significant role in designing new technology and defining indications for its use, practitioners need to evaluate and determine the most efficacious treatments for their patients. Neurointerventional Surgery: An Evidence-Based Approach by renowned endovascular neurosurgeons Min Park, M. Yashar S. Kalani, and Michael F. Stiefel examines the mo.